Investigation of Functional Group Effects on Palladium Catalysed Asymmetric P–H Addition - Li, Xi-Rui (2016)
The pincer catalysed asymmetric P–H addition of diphenylphosphine to 3-benzylidene-2,4-pentadione is herein reported. Albeit successful in catalysing a series of similar substrates, unexpected chelation of the dione substrate to a CP and CN palladacycle catalyst resulted in inactivation of the catalyst with adjacent coordination sites. Protected phosphine adducts were isolated and characterised, providing critical insights to the choice of catalyst for structurally distinct functional groups borne by the substrate.